Análise espacial da ocorrência de Leishmaniose Visceral no Brasil - FONTOURA, Iolanda Graepp (2018)
Human Visceral Leishmaniasis (HVL) is a disease of great epidemiological significance, becoming a public health problem, with high morbidity and mortality rates; and in regions where the geographical overlap of HVL and of human immunodeficiency virus (HIV) occurs, these indexes are even higher. This study was aimed to identify spatial patterns of the distribution of visceral leishmaniasis in Brazil between the years 2001 and 2015. The methodology used was an ecological and exploratory study, using the geoprocessing tools to design thematic maps, which were drawn up by the TerraView 4.2.2 software, with secondary data obtained from the Brazilian Institute of Geography and Statistics (IBGE) and from the Department of Informatics of the Brazilian Unified Health System (DATASUS). This software allowed us to obtain the Moran global – I and Moran local – LISA values. A total of 53,994 cases of visceral leishmaniasis were reported during the study period between 2001 and 2015, with an average annual rate (AAR of 2,59/100,000 inhabitants (inhab.)); male gender, 33,502 (62%, AAR of 2,43/100,000 inhab.); higher incidence among indigenous people (AAR of 2,91/100,000 inhab.); age range prevalent between 1 and 4 years (30%); increased incidence in <1 year (AAR of 3,76/100,000 inhab.); 3,589 deaths (rate of 0,12/100,000 inhab.); greater proportion in the Northeast region, 29,968 (56%); higher incidence in the North region (AAR of 7,04/100,000 inhab.). Maranhão was the prevalent, with 8,194 (15%) of the notified cases; highest index in the state of Tocantins (AAR of 21.65/100,000 inhab.); 2,231 cases of HVL/HIV coinfection in the study period between 2007 and 2015 (AAR of 13/100,000 inhab.), in 204 Brazilian municipalities (4%). The main epidemiological characteristics of the cases of HVL/HIV coinfection were: it mainly affects men (77%; AAR of 0.20/100,000 inhab.); prevalent in the age range between 20 and 39 years (51%), with higher AAR between 40 and 59 years (AAR of 0.20/100,000 inhab.); it is mainly concentrated in the Northeast region (51%), with higher AAR in the Midwest region (AAR of 0.26/100,000 inhab.); increased concentration of cases in Minas Gerais (17%), with higher AAR in the state of Mato Grosso do Sul (AAR of 1.17/100,000 inhab.). The Moran global index was 0.46 (p<0.01), which indicated similarities between municipalities with a presence of significant spatial autocorrelation. It was possible to note the presence of similar clusters among the surrounding municipalities in the thematic maps of HVL, Canine Visceral Leishmaniasis (CVL), HVL/HIV, HIV, garbage, without sewage network, and lower human development index (HDI). The maps of Moran Map related to the Northeast region, part of the Midwest region, part of the North region and LISA Map showed statistically significant clusters (p<0.001). We conclude that the geoprocessing technique allowed us to detect and analyze the clusters of HVL rates with the proposed variables, as well as the places with higher and lower intervention needs. It was possible to note a gradual decrease in the AAR of HVL, maintenance of mortality rates and slight decrease in the AAR of new cases, but a significant increase in the number of cases of HVL/HIV coinfection